2003
DOI: 10.1248/bpb.26.1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low-density Lipoproteins: What Is Understood and What Remains to Be Clarified.

Abstract: Oxidized low-density lipoprotein (OxLDL) has previously been thought to promote atherogenesis through foam cell formation. However, the actual nature of OxLDL present in vivo remained obscure until recently. We have produced a monoclonal antibody, DLH3, which specifically binds to OxLDL but not to native LDL. The presence of OxLDL in the LDL fraction of human plasma was demonstrated by introducing a sandwich ELISA procedure using DLH3 together with an anti-apoB antibody. Furthermore, OxLDL levels appeared to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 68 publications
2
79
0
6
Order By: Relevance
“…It has been widely assumed that circulating blood is not a site of LDL oxidation, since serum has strong anti-oxidative abilities [24]. It is possible that glycoxidised LDL is formed in the subendothelial space of the vessel and enters the circulation by backward diffusion from stable atherosclerotic lesions, or by release from unstable atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely assumed that circulating blood is not a site of LDL oxidation, since serum has strong anti-oxidative abilities [24]. It is possible that glycoxidised LDL is formed in the subendothelial space of the vessel and enters the circulation by backward diffusion from stable atherosclerotic lesions, or by release from unstable atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…PON1 is synthesized and secreted by liver and mostly located on HDL surface (Mackness et al 1996). LDL oxidation has an important role in development and progression of coronary artery disease (Itabe 2003). PON1 inhibits LDL oxidation (Mackness et al 1996).…”
Section: Dietary Intervention and Study Protocolmentioning
confidence: 99%
“…In addition, several studies have demonstrated the antioxidative properties of statins 6,11) , andithaspreviouslybeenshown,bothinvitroandin vivo, that statins inhibit lipid and lipoprotein oxidation, thereby suppressing ROS formation and/or bluntingthedamagingeffectsoftheseradicals 6,12) . The oxidative modification of LDL particles in thevesselwallplaysacriticalroleinthedevelopment of atherosclerosis 13,14) . Therefore, reducing oxidized LDL is a potentially effective method for mitigating the atherogenicity of LDL particles.…”
Section: Cardiovascular Disease Lipid Oxidation and Oxidized Ldlmentioning
confidence: 99%
“…Several in vitro studies have shown that lipid-laden foam cells are formed after macrophages take up oxidized LDL 10,28,29) . In addition, the presence of lipid-laden foam cells is a typical feature of vulnerable atherosclerotic lesions.Therefore, the oxidativemodificationofLDLplaysaroleinthedevelopmentofatheroscleroticlesionsviatheformationof foamcells 13) .Recentevidenceindicatesthatmodified apolipoproteinBderivedfromoxidizedLDLaccumulates in foam cells 29) . Furthermore, macrophagederivedfoamcellscontainmanylipiddropletsinthe cytoplasm, and the levels of oxidized LDL are increased in patients with a history of acute myocardialinfarctionandcarotidarteryatherosclerosis 28,[30][31][32] .…”
Section: Cardiovascular Disease Lipid Oxidation and Oxidized Ldlmentioning
confidence: 99%